EXPLORING THE MULTIGENERATIONAL INFORMATION LITERACY GAP IN DIGITAL SOCIETY - M Nur Rahmat Achdar HT; Megawati Megawati; Jumiati Jumiati; Andi Mudassir; Hazan Hazan (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
Digital transformation has expanded access to information across generations while simultaneously creating significant literacy gaps. This study explores the meanings, strategies, causal factors, and expectations regarding information literacy in Indonesia's digital society. Using a qualitative exploratory design, data were collected from 25 purposively selected informants representing Generation Z, Millennials, Generation X, and Baby Boomers in Bone Regency through in-depth interviews and thematic analysis. The findings reveal that younger generations (Gen Z and Millennials) are generally more active and critical in seeking, verifying, and comparing digital information, whereas older generations (Gen X and Baby Boomers) rely more on traditional sources and close social networks. Motivational barriers, cognitive limitations, and socio-cultural influences emerged as the main drivers of this literacy gap. Despite these differences, all generations expressed aspirations for strengthening inclusive literacy through training, intergenerational collaboration, and community-based discussion forums. By integrating the ACRL Information Literacy Framework, Generational Theory, and the Socio-Technical Gap Model, this study provides a comprehensive theoretical lens to explain variations in literacy practices and challenges across generations. The results contribute to theory by contextualizing multigenerational digital literacy within semi-urban Indonesian society, and to practice by offering actionable recommendations for literacy training programs, intergenerational mentoring, and policy interventions that foster inclusive and sustainable information ecosystems. These insights underscore the urgency of adaptive, participatory, and culturally responsive strategies to bridge the gap and build societal resilience in the face of accelerating digital information flows